The Effect of the Educaplay Platform on Students’ Interest in Learning Arabic - Sarif, Suharia; Dunggio, Mohamad Faturrahman; Binti Hj. Bahri, Ratni; Safii, Randi; Waeduereh, Mustafakama; Muhammad Anas bin Al Muhsin (Langkawi: Journal of The Association for Arabic and English, 2026)
This study was motivated by students’ low interest in learning Arabic at MAN 1 Kota Gorontalo and the need for more interactive instructional media to address a classroom atmosphere that was often monotonous. The study aimed to identify and verify the effect of the Educaplay platform on students’ interest in learning Arabic, to compare students’ learning interest between the experimental and control classes, and to identify the contribution of Educaplay’s interactive and game-based features to creating more engaging and effective Arabic instruction. This study employed a quantitative approach using a quasi-experimental nonequivalent control group design. The participants were 60 eleventh-grade students divided into an experimental class and a control class, with 30 students in each group. Data were collected through a Likert-scale questionnaire, classroom observation, structured interviews, and pre-test and post-test measures. The data were then analyzed using SPSS 26 through validity and reliability testing, descriptive statistics, normality and homogeneity testing, and an independent-samples t-test. The findings showed that the mean score of students’ learning interest in the experimental class was higher than that of the control class, namely 81.20 compared to 74.85, with a significance value of 0.002 < 0.05. These findings indicate that the use of Educaplay had a significant effect on students’ interest in learning. Therefore, Educaplay was shown to create more interactive, enjoyable Arabic learning experiences that encourage more active student engagement.